Comparison between two types of computer for Industrial Ethernet performance - Handy, Ali Munir; Nordin, Saad, Assoc. Prof. Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Ahmad Mujahid, Ahmad Zaidi, Dr.; Muhammad Kamarul, Baharin (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/